Anolyte Enhances Catalyst Utilization and Ion Transport Inside a CO2 Electrolyzer Cathode. Issue 1 (1st January 2023) - Saha, Prantik; Henckel, Danielle; Intia, Fry; Hu, Leiming; Van Cleve, Tim; Neyerlin, K. C.
Abstract : Electrochemical CO2 reduction is a promising technology to capture and convert CO2 to valuable chemicals. High Faradaic efficiencies of CO2 reduction products are achieved with zero-gap alkaline CO2 electrolyzers with a supporting electrolyte at the anode (anolyte). Herein, we investigate the effect of anolyte on the electrode properties such as catalyst utilization, ionic accessibility etc. of a CO2 reduction cathode using electrochemical techniques and cell configurations that avoid the complexities related to co-electrolysis. Using 1M KOH as the anolyte and a Cu gas-diffusion-electrode with low Nafion content as the model CO2 reduction electrode, we find that electrode capacitance (proxy for electrochemically active surface area) and ionic conductivity inside the cathode increase approximately 4 and 447 times, respectively, in presence of KOH. Liquid anolyte wets the electrode's pore structure more efficiently than capillary condensation of feed water vapor. The ionomer coverage is very low, and its distribution inside the electrode is highly fragmented. Surface ion conduction mechanisms inside the electrode are orders of magnitude lower than the bulk ion conduction in presence of anolyte. This study shows that when an anolyte (e.g., KOH) is used, catalyst utilization and ionic accessibility inside the electrode increase significantly.